Role of Regional Language Background and Speech Styles on the Production of Voice Onset Time (VOT) in English among Indonesian Multilinguals - Zen, Evynurul Laily (Indonesian Journal of Applied Linguistics, 2020)
This paper seeks to contribute to the nature of cross-linguistic transfer in the production of English Voice Onset Time (VOT) by adult multilingual speakers in Indonesia in view of how different regional home languages and speech settings shape the phonetic realizations. Three adult multilinguals participated in this pilot project. They are all learners of English as the third language (L3) at the Department of English of a state university in Malang, Indonesia who acquire different regional home languages – Javanese, Sundanese, and Madurese – as the first language (L1) and speak Indonesian as the second language (L2). The participants’ production of bilabial stop consonants of English /p/ and /b/ were elicited from two different speech settings; a careful speech via text readings (monologue and dialogue) and wordlist reading, and a spontaneous speech through natural conversation among participants. 21 tokens from each participant were then analyzed acoustically in Praat. The findings show that the bilingual speaker with L1 Sundanese consistently produced the shortest VOT values of both /p/ and /b/. The Javanese speaker produced the intermediate lag, whereas the Madurese speaker produced the longest aspiration interval. It is shown that the Sundanese language provides the strongest transfer effect, while Madurese gives the least effect. In light of cross-linguistic transfer, however, the overall VOT productions clearly put forth evidence of L1 phonological transfer. The production of non-native bilabial stop VOTs of English is largely due to the absence of this phonetic property in Javanese and Sundanese while Madurese shows marginal similarities. The findings also demonstrate that speech styles play only a marginal role in determining the production of VOTs that the VOTs of /p/ and /b/ in careful speech is found to be slightly longer than in the spontaneous settings. This study makes an original contribution to the area of phonological acquisition in adult speakers by giving attention to the understudied languages of Indonesia in order to more fully understand the interaction of different language systems in multilingual language acquisition and development.